Let's go through the operations step-by-step, simplifying each one as we go, ensuring that we leave answers in their simplest form.
-
Simplify \( \sqrt{108} \): \[ \sqrt{108} = \sqrt{36 \cdot 3} = \sqrt{36} \cdot \sqrt{3} = 6\sqrt{3} \]
-
Calculate \( \sqrt{15} \cdot \sqrt{5} \): \[ \sqrt{15} \cdot \sqrt{5} = \sqrt{15 \cdot 5} = \sqrt{75} = \sqrt{25 \cdot 3} = \sqrt{25} \cdot \sqrt{3} = 5\sqrt{3} \]
-
Simplify \( \frac{12}{2\sqrt{3}} \): \[ \frac{12}{2\sqrt{3}} = \frac{6}{\sqrt{3}} \cdot \frac{\sqrt{3}}{\sqrt{3}} = \frac{6\sqrt{3}}{3} = 2\sqrt{3} \]
-
Simplify \( 4\sqrt{3} + \sqrt{27} \): \[ \sqrt{27} = \sqrt{9 \cdot 3} = \sqrt{9} \cdot \sqrt{3} = 3\sqrt{3} \] Thus, \[ 4\sqrt{3} + \sqrt{27} = 4\sqrt{3} + 3\sqrt{3} = 7\sqrt{3} \]
-
Calculate \( 3\sqrt{12} - 2\sqrt{3} \): \[ \sqrt{12} = \sqrt{4 \cdot 3} = \sqrt{4} \cdot \sqrt{3} = 2\sqrt{3} \] Hence, \[ 3\sqrt{12} = 3 \cdot 2\sqrt{3} = 6\sqrt{3} \] Therefore, \[ 3\sqrt{12} - 2\sqrt{3} = 6\sqrt{3} - 2\sqrt{3} = 4\sqrt{3} \]
-
Simplify \( \sqrt{75} \): \[ \sqrt{75} = \sqrt{25 \cdot 3} = \sqrt{25} \cdot \sqrt{3} = 5\sqrt{3} \]
-
Perform the calculation \( 4\sqrt{3} + \sqrt{27} + 3\sqrt{12} - 2\sqrt{3} \): From previous calculations: \[ 4\sqrt{3} + 3\sqrt{27} = 7\sqrt{3} \] and \[ 3\sqrt{12} - 2\sqrt{3} = 4\sqrt{3} \] Therefore: \[ 4\sqrt{3} + 3\sqrt{12} + \sqrt{27} - 2\sqrt{3} = 7\sqrt{3} + 4\sqrt{3} = 11\sqrt{3} \]
-
Simplify \( \frac{6\sqrt{3}}{3} \): \[ \frac{6\sqrt{3}}{3} = 2\sqrt{3} \]
Putting this information together, we have simplified various expressions and combined their results. The final answers are as follows:
- \( \sqrt{108} = 6\sqrt{3} \)
- \( \sqrt{15} \cdot \sqrt{5} = 5\sqrt{3} \)
- \( \frac{12}{2\sqrt{3}} = 2\sqrt{3} \)
- \( 4\sqrt{3} + \sqrt{27} = 7\sqrt{3} \)
- \( 3\sqrt{12} - 2\sqrt{3} = 4\sqrt{3} \)
- \( \sqrt{75} = 5\sqrt{3} \)
- \( 4\sqrt{3} + 3\sqrt{12} + \sqrt{27} - 2\sqrt{3} = 11\sqrt{3} \)
- \( \frac{6\sqrt{3}}{3} = 2\sqrt{3} \)